Improved localisation of neoclassical tearing modes by combining multiple diagnostic estimates. (24th May 2017) - Rapson, C.J.; Fischer, R.; Giannone, L.; Maraschek, M.; Reich, M.; Treutterer, W.
Abstract: Neoclassical tearing modes (NTMs) strongly degrade confinement in tokamaks, and are a leading cause of disruptions. They can be stabilised by targeted electron cyclotron current drive (ECCD), however the effectiveness of ECCD depends strongly on the accuracy or misalignment between ECCD and the NTM. The first step to ensure minimal misalignment is a good estimate of the NTM location. In previous NTM control experiments, three methods have been used independently to estimate the NTM location: the magnetic equilibrium, correlation between magnetic and spatially-resolved temperature fluctuations, and the amplitude response of the NTM to nearby ECCD. This submission describes an algorithm which has been designed to fuse these three estimates into one, taking into account many of the characteristics of each diagnostic. Although the method diverges from standard data fusion methods, results from simulation and experiment confirm that the algorithm achieves its stated goal of providing an estimate that is more reliable and accurate than any of the individual estimates.